Ferromagnetism and Magnetoresistance of Cobalt-Silicon Alloy in Early Stages of Ball Milling - Chitnarong Sirisathitkul (Science Faculty of Chiang Mai University, 2019)
The potential applications in hydrogen storage and giant magnetoresistance (GMR) devices have led to investigation of cobalt-silicon (Co-Si) alloys. By ball-milling amount fractions of 40 % cobalt (Co) and 60 % silicon (Si) powders for 1-3 h, crystalline fcc and hcp Co as well as fcc Si phases were detected without impurity phase. All three samples exhibited ferromagnetism with increasing magnetizations with increasing milling time due to the reduction in magnetocrystalline anisotropy. The 0.4% decrease in an electrical resistance of the pressed 3 h-milled powders under an 11 kOe-magnetic field was attributed to the GMR effect. Since the GMR mainly arises from the spin-dependent scattering across magnetic Co/semiconducting Si interfaces, the room temperature GMR ratio was reduced with increasing grain sizes in the case of 2 and 1 h. From these results, this functional material is attractive for its combination of electromagnetic with electrochemical properties.